Antibiotic resistance of microflora to drugs in case of conjunctivitis of cats of bacterial origin - N. Krivenko; I. Rublenko; S. Rublenko; V. Koziy; R. Shaganenko; O. Gorbatiuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2023)
Currently, the most common ophthalmic pathology in cats is inflammatory processes. Pathologies are observed frequently and regardless of breed, sex, and age. The causes of the disease are the prevalence of infections affecting the visual analyzer, inadequate care of their pets by the owners, untimely visits to a veterinarian, etc. It is essential to diagnose the cause of inflammation of the ocular mucosa in time, as knowing the etiology of the disease is necessary to prescribe effective treatment, which can lead to complications. Bacteriological tests play an important role, allowing us not only to identify the pathogen but also to determine its sensitivity or resistance to a particular drug, to prescribe effective treatment in time, to reduce the economic costs of treatment, the treatment period, etc. Most of the microorganisms that can be found in the conjunctival sac are non-pathogenic, although some of them are opportunistic. The study was conducted at the VetExpert veterinary center on cats of all ages and sexes with signs of conjunctivitis during 2022–2023. Out of 473 cats examined, cases of eye disease were detected in 105 cats or 22.1 % of the total number of ophthalmopathology cases. According to the results of the research, it was found that conjunctivitis was caused by Staphylococcus aureus, Staphylococcus epidermidis, Nonhaemolytic Streptococcus, and Pseudomonas aeruginosa. In treating conjunctivitis of bacterial etiology, topical application of the drug and systemic antibiotic therapy should be prescribed. In treating cats with bacterial conjunctivitis, systemic drugs, and antibiotic therapy should be prescribed. Antibiotics and antibacterial drugs should be prescribed only based on the results of bacteriological examination and antibioticogramа.